Assessment Of Felt Needs and Effect of Health Education Intervention on Knowledge Regarding Reproductive Health of School Students in A Slum in Mumbai - Padhyegurjar , Manasi S; Padhyegurjar , Shekhar B; Adsul , Bal K (National Journal of Community Medicine, 2012)
Objectives: To assess the felt needs, level of knowledge and the impact of health education sessions over the period of one year regarding reproductive health among ninth standard school students of a slum area in Mumbai. Material and Methods: The study is school based interventional follow up study.Health education sessions on reproductive health were conducted. Pre test, immediate post test, along with a follow up post test at six months and one year after intervention were administered. SPSS Version 17 and Excel software were used for analysis. Paired‘t’ test and Chi-square test were applied. Results: Base line knowledge in all aspects of reproductive health was observed to be very low as compared to the post tests. Knowledge was retained over the period of one year in questions pertaining to physical changes in boys and girls, female anatomy and role of female in sex determination.However significant loss (p<0.01) of the acquired knowledge was observed in questions pertaining to hormones, night emissions and masturbation. Need for sex education was perceived by 99.24 % students. Preferred class for initiation were sixth and seventh (24.09% and 43.39% respectively). Doctors (83.02%) were the most preferred sources of information. Conclusions: Health education sessions are very effective in increasing knowledge. However, students tend to lose information regarding certain aspects as time progresses. Students are in need of scientific information from lower classes.